Effect of different washing methods on denim fabric properties and their effluent’s environmental impact - Hafsa Jamshaid; Abdul Waqar Rajput; Ijaz Bajwa; Abdul Mujeeb (Mehran University Research Journal of Engineering and Technology, 2023)
Nowadays, denim is in trend. To achieve visually appealing results, various washing processes are applied to denim. For washing denim, a variety of methods are available, and they all produce distinct kinds of waste. These methods have various environmental effects. This study aims to examine the environmental impact of various denim washing effluents. Here, six different washes desizing, enzyme, stone, bleach, acid, and random wash are performed. In order to compare how washing affects both the environment and the fabric, effluent tests are carried out. Since enzymes are unique by nature, enzyme wash demonstrated the greatest GSM. They don't affect the fibre composition; they just break down the color that is on the surface of the cellulose. Shrinkage is the cause of the general rise in GSM. However, the thickness, pilling, and elongation % of the cloth were unaffected by the washing. Due to the alkaline nature of the washing procedure, which results in minimal harm to the cloth, the enzyme and desize wash exhibit high strength. The fabric's rigidity decreases when stone, bleach, and acid wash damage it, which raises the angle at which the crease recovers. Due to the use of enzyme and desize wash produces effluent with a reduced TDS. In these procedures, the indigo hue on the denim surface is diminished, which causes the fading to occur. This process results in less polluted water that is simpler for wastewater treatment plants to process.